Elements of Family-Centered Care in the Pediatric Intensive Care Unit: An Integrative Review. Issue 3 (June 2017) - Richards, Claire A.; Starks, Helene; O'Connor, M. Rebecca; Doorenbos, Ardith Z.
Abstract : This article reports results from a systematic search and thematic analysis of qualitative literature to identify key issues related to family-centered care, behaviors, and communication skills that support the parental role and improve patient and family outcomes in the pediatric intensive care unit. Five themes were identified: (1) sharing information, (2) hearing parental voices, (3) making decisions for or with parents, (4) negotiating roles, and (5) individualizing communication. These themes highlight several gaps between how parents want to be involved and how they perceive clinicians' engagement with them in the care of their child. Parental preferences for involvement differ in the domains of information sharing, decision making, and power sharing across a spectrum of parental roles from parents as care provider to care recipient. The pediatric intensive care unit setting may place clinicians in a double bind trying to both engage families and protect them from distress. Asking families of critically ill children about their preferences for participation across these domains may improve clinician-family relationships.